Assessing the Implementation of a Culinary Skills Program in Vocational High School: A CIPP Model Evaluation - Ade Hari Fitri; Ernawati Ernawati; Elida Elida; Muhammad Giatman (STAI Hubbulwathan Duri, 2025)
The Culinary Expertise Program at SMKN 1 Luak, established in 2015, aims to equip students with professional skills for employment or entrepreneurship. However, tracer studies from 2021 to 2023 indicate that a significant number of alumni are unemployed or work outside their field, raising concerns about program effectiveness. This study employed the CIPP (Context, Input, Process, Product) evaluation model using a mixed-methods approach. Quantitative data were collected from 87 alumni through questionnaires, while qualitative insights were obtained from six purposively selected school stakeholders via semi-structured interviews. Data were analyzed using descriptive statistics and thematic analysis. The overall program scored 76.60%, indicating moderate appropriateness. The context dimension, including alignment with school vision and graduate needs, was rated as appropriate. The input component revealed moderate curriculum relevance and inadequate infrastructure, particularly a lack of standard practice facilities. The process evaluation showed that theory-based instruction was implemented effectively, but practical learning activities were constrained by limited resources. The product aspect received positive ratings, with most students meeting skill competency standards and obtaining certification, although graduate employment outcomes remain suboptimal. While the program meets several of its educational objectives, gaps remain in curriculum-industry alignment, infrastructure adequacy, and student motivation. Strengthening partnerships with industry, revising the curriculum to match labor market demands, and investing in hands-on learning facilities are essential to improve graduate employability and program impact.